Convexity-preserving Bernstein–Be´ zier quartic scheme - Hussain, Maria; Majid, Ahmad Abd; Hussain, Malik Zawwar (Elsevier, 2014)
A C1 convex surface data interpolation scheme is presented to preserve the shape of scattered data arranged over a triangular grid. Bernstein–Be´ zier quartic function is used for interpolation. Lower bound of the boundary and inner Be´zier ordinates is determined to guarantee convexity of surface. The developed scheme is flexible and involves more relaxed constraints.